Peran penggunaan fintech dan e-commerce dalam menunjang perkembangan UMKM - Ulya, Desi Zulfatul; Astuti, Ratna Fitri; Sudarman, Sudarman; Sutrisno, Sutrisno (Journal of Economics Research and Policy Studies, 2025)
The use of digital technology such as fintech and e-commerce is growing and provides various conveniences for Micro, Small and Medium Enterprises (MSMEs) in managing businesses. The increasing use of digital technology has a significant impact on the way MSMEs access financial services, market products, and reach consumers more broadly. The use of fintech can help MSME players manage financial transactions efficiently, while e-commerce opens up wider marketing opportunities without being limited to one region. The research was conducted to determine the effect of the use of fintech and e-commerce on the development of MSMEs. The study used a causal associative research type, with a quantitative approach. The number of samples used was 54 MSME players who work in Marimar. Data collection techniques were carried out by distributing questionnaires, while data analysis used multiple linear regression analysis techniques. Based on the results of the study, it is found that there is a partial and significant influence between the use of fintech and e-commerce on the development of MSMEs. The use of fintech and e-commerce simultaneously has a significant effect on MSME development variables.